Crossing the bridge: the educational leadership of First Nations Women - Umpleby, Sandra Lynne (2007)
ABSTRACT In North West British Columbia, First Nations women are playing an essential role in a cultural shift that is positively affecting community health and the education of Aboriginal youth. Historically, the First Peoples of the North West coast were profoundly transformed by European contact. Policies, oppressions and disease disrupted lives and communities that had existed in stasis since time immemorial. The results, described by Thomas Berger as “third world” conditions, are predictable --young and old afflicted with addictions and dysfunctions. Recently, the dominant politics have begun to acknowledge the First Nations as having a legitimate voice in the social and political processes that concern them. This research is one part of the national multi-disciplinary study, Coasts Under Stress: The Impact of Social and Environmental Restructuring on Environmental and Human Health in Canada. In this phase of the larger project, the importance of the educational and community leadership of First Nations women is recognized as they struggle to break cycles of dysfunction that afflict their communities. Increasing enrollment of coastal youth and adults in secondary school and college programs, and in educational programs on reserve over the past decade is one sign of positive change. The main purpose of my study is to explore the role of First Nations women in supporting social and educational opportunities in their villages and in society-at-large. The central research question asks what supports and barriers First Nations women encounter as they assume leadership roles within their villages and without. A purposive sample of seven women joined the research conversation, involved because of the formal leadership roles they have assumed, and because of their perceived influence on the general health of their communities and the region. Their responsibilities represent a wide spectrum of educational and community leadership, and counter a prevailing stereotype of First Nations people generally and women ...